ANALISA SERANGAN SQL INJEKSI MENGGUNAKAN SQLMAP - Lika, Sudiharyanto; Halim, Roy Dwi Putra; Verdian, Ihsan (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
In today's world, SQL injection is a serious security threat on the Internet for various dynamic web sites on the internet. Because internet usage for various online services is increasing, so are the security threats that exist on the web are increasing. SQL injection attack is one of the most serious security vulnerabilities on the Web, most of these vulnerabilities are caused by a lack of input validation and use of SQL parameters. SQLMap is an application of the Kali Linux operating system where this application is useful for injecting data contained in a web using the features available in this application. In this paper, we have presented an example of an attack case using SQLMAP, starting from the injection process and how the application works until the process where we can get sensitive data from a web that has been injected without the victim knowing.